On the local self-government organisation in the public authority unified system - N. N. Musinova (Вестник университета)
A significant form of constitutional rights implementation by Russians is the institution of local self-government, which has an important role to play in the civil society formation. Federal Law dated on December 21, 2021, No. 414-FZ “On the General Principles of the Organisation of Public Power in the Constituent Entities of the Russian Federation” reveals the constitutional provisions for the public power unified system organisation in the constituent entities of the Russian Federation. Currently, a draft federal law reflecting the general principles of the local self-government organisation in the public power single system is being discussed. The article analyses the main provisions of this draft law related to the public self-government development, civil society and the representative power formation at the municipal level and identifies their imperfections.